Inclusive education in the republic of Kazakhstan and factors affecting its development - Turlubekova, M.B.; Bugubaeva, R.O.; Besspayeva, R.S. (BUKETOV BUSINESS REVIEW, 2021)
Object: is the system of inclusive education in the context of state management policy. The methods: The following methods were used in the study: theoretical, empirical methods, methods of highquality data processing, methods of mathematical and statistical processing: ranking, correlation. An econometric model was constructed to test the hypothesis that there is a relationship between the growth rate of the number of children enrolled in inclusive education and the growth rate of the number of teachers in general education schools. The conclusions and results of the study were presented using a graphical method of presenting the results obtained. Findings: The author hypothesized that there is a relationship between the growth rate of the number of children enrolled in inclusive education and the growth rate of the number of teachers in general education schools. To prove or refute this hypothesis, the author conducted a regression analysis, which resulted in the conclusion that an increase in the number of teachers in general education schools is a significant and necessary condition for the further development of inclusive education. Conclusions: Based on the regression analysis, the author of the article concluded that the increase in the number of teachers of general education schools contributes to an increase in the number of children enrolled in inclusive education. The research analysis on the studied problem shows that at the present stage inclusion is the leading trend in the development of the education system. The quality of the development of inclusive education in Kazakhstan raises many questions for researchers, including the ineffectiveness of the use of innovative forms of education in inclusive education, the lack of knowledge of international experience, etc.